PENGARUH LEADER-MEMBER EXCHANGE TERHADAP EFFORT BEHAVIOR DAN SERVICE SABOTAGE DENGAN DEPRIVASI RELATIF SEBAGAI PEMEDIASI PADA KARYAWAN FRONTLINER HOTEL DI BANDA ACEH - Vera Rawinda, Sofyan Idris (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study aims to determine the effect of leader-member exchange on effort behavior and service sabotage with relative deprivation as a mediator. Empirical study was conducted on frontline employees in three-star hotel in Banda Aceh using questionnaires as research instruments, in which the sample in this study is 113 respondents. Probability Sampling is used as sampling technique with Simple Random Sampling method. The Hierarchical Linear Modeling (HLM) method was used as a data analysis method using the IBM SPSS 20 software. The results of this study indicate that the leader-member exchange have a positive and significant effect on effort behavior and service sabotage and relative deprivation. Relative deprivation has positive and significant influence on service sabotage. In addition to the results obtained that relative deprivation mediate the positive influence of leader-member exchange on effort behavior and service sabotage. Keywords: Leader-Member Exchange, Effort Behavior,Service Sabotage, Relative Deprivation